2011
DOI: 10.1097/aog.0b013e31820b3c61
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiple Marker Test for Ectopic Pregnancy

Abstract: : ClinicalTrials.gov, www.clinicaltrials.gov, NCT00194168.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 35 publications
7
65
0
1
Order By: Relevance
“…The previous predictive model of EP was based on the combination of two decision trees (10). One decision tree was developed to maximize the sensitivity of prediction, and the second to maximize specificity of prediction for the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous predictive model of EP was based on the combination of two decision trees (10). One decision tree was developed to maximize the sensitivity of prediction, and the second to maximize specificity of prediction for the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Overall accuracy in those classified, and accuracy of each predicted outcome (ie. EP or IUP) is then reported (10, 18). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Dewan and co-workers reported that a copy-number deletion of PSG11 and its alternatively spliced variants may confer risk for preeclampsia but further studies are required to confirm their findings (Zhao et al, 2012). Expression of some PSGs has been reported in molar trophoblastic tissue (Hagiwara et al, 1986, Leslie et al, 1990 and differential expression of PSGs in intrauterine pregnancy and ectopic pregnancy have been recently suggested to have useful diagnostic value as part of a multiple biomarker test (Rausch et al, 2011). In summary, while low PSG concentrations appear associated with some pregnancy complications, studies with more specific reagents are required as PSG levels could potentially be used as useful markers of placental function.…”
Section: Psgs and Pregnancy Pathologiesmentioning
confidence: 99%